Współczesne teorie społeczeństwa obywatelskiego w świetle nowego materializmu - Pietrzak, Edyta (Eastern Review, 2017)
The article discusses contemporary theories of civil society at the local, global and transnational level with reference to one of the most interesting modern trends in humanities – the concept of new materialism. The proposed classification has been based on the criterion of civil rights expansion suggested by Reinhardt Koselleck.